2015
DOI: 10.1016/j.ifacol.2015.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Control by state observer of PEMFC anodic purges in dead-end operating mode

Abstract: International audienceA Proton Exchange Membrane Fuel Cell (PEMFC) needs an active system to control all the ancillaries and ensure optimal operating conditions, especially in a fuel cell vehicle. For the fuel cell system architecture, dead-end anode is the cheapest architecture for the hydrogen line and also the one that leads to important reversible and irreversible degradations if not appropriately managed. To address the cost and durability issues on fuel cell vehicles, this study proposes a state observer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The nitrogen cross-over and accumulation in the anode depends on membrane temperature and hydration level and the current density. 43,54,55 Mittlesteadt and Umbrell 56 have devised a simple method to measure nitrogen crossover as a function of temperature, RH, and the equivalent weight (EW) of the membrane material. They found that nitrogen crossover could be represented as two parallel processes representing nitrogen transport through the polymer and nitrogen transport through the water phase of the ionomer.…”
Section: Research Gap To Be Addressed By This Studymentioning
confidence: 99%
“…The nitrogen cross-over and accumulation in the anode depends on membrane temperature and hydration level and the current density. 43,54,55 Mittlesteadt and Umbrell 56 have devised a simple method to measure nitrogen crossover as a function of temperature, RH, and the equivalent weight (EW) of the membrane material. They found that nitrogen crossover could be represented as two parallel processes representing nitrogen transport through the polymer and nitrogen transport through the water phase of the ionomer.…”
Section: Research Gap To Be Addressed By This Studymentioning
confidence: 99%
“…where zðtÞb  eðtÞ T ;x 2 ðtÞ;x 4 ðtÞ Ã T , and the coefficient matrix H ¼ fh ij g2ℝ 5Â5 ði; j ¼ 1; 2; …; 5Þ and the vector L2ℝ 5Â1 can be obtained and expressed as follows by substituting (26) into (13), (27) into (15), and (20) into the derivative of (19), respectively: …”
Section: Stability Analysismentioning
confidence: 99%
“…Then, based on the fact that Q v is positive definite, (30), and (31), _ VðtÞ is negative. Therefore, from the previous facts, the errors  eðtÞ T ;x 2 ðtÞ;x 4 ðtÞ Ã are uniformly ultimately bounded under the regulation of the control law (26) and (27) [34].…”
Section: Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A previous work with the same purpose has been presented in [13] with the UKF technique (Unscented Kalman Filter) for the observer instead of sliding mode. This UKF observer is difficult to tune for a specific (P,T) couple with no theoretical proof of convergence.…”
Section: Introductionmentioning
confidence: 99%